Buzz Group Method to Improve Exclusive Breastfeeding Self-Efficacy in Pregnant Women - Nimah, Lailatun; Pradanie, Retnayu; Pradanie, Retnayu; Cahyanti, Febyana Dwi; Cahyanti, Febyana Dwi (International Journal of Psychosocial Rehabilitation, 2020)
Exclusive breastfeeding for six months is an attempt to increase the benefits of breastfeeding and to reduce infant mortality rate. Pucang Sewu Community Health Center had exclusive breastfeeding coverage value of 48.08% in 2016, and has not yet reached the national target of 80%. This research is aimed to identify the level of self-efficacy before and after applying modified buzz group method and to analyze the influence of modified buzz group method about exclusive breastfeeding to self-efficacy of pregnant women. Modified buzz group method was conducted in Pucang Sewu Community Health Center. This study was designed using quasi-experimental design. The population was 42 pregnant women. A total sample of 38 respondents was taken using purposive sampling. BSES-SF (Breastfeeding Self-Efficacy Scale Short Form) questionnaire was administered at pre-test and post-test. Data analysis was performed using Wilcoxon Signed Rank test and Mann Whitney test. The results showed that Wilcoxon Signed Rank statistic test obtained p-value of 0.000 in the treatment group and p-value of 0.355 in the control group. Mann Whitney statistic test obtained significant value of p=0.000 in treatment and control group. Modification of buzz group method took effect to improve self-efficacy about exclusive breastfeeding for pregnant women because this method is organized by four sources of self-efficacy - direct experience, indirect experience, verbal persuasion, and emotional condition. Modification buzz group method improved exclusive breastfeeding self- efficacy in pregnant women coverage in Surabaya, especially Pucang Sewu Community Health Center.